Transformação integral em domínio único aplicada à engenharia de reservatórios - Pelisoli, Leonardo Osório (2019)
In the domain of Reservoir Engineering, pressure transient analysis and well test analysis are terms used to describe the set of tools and techniques enabling reservoir characterization through specialized operations known as well tests. The physics of these operations is modeled by the Diffusivity Equation, whose particular solutions for appropriately simplified situations are used to understand and quantify flow behavior within the reservoir, and in this way to gain information about the reservoir itself. In this work, the Generalized Integral Transform Technique (GITT) is applied for the first time in the solution of the continuous point source problem in a heterogeneous tridimensional reservoir. The exact transient solution of a simpler auxiliary problem — the same continuous point source, but in a homogeneous reservoir — is used as an analytical filter in order to improve the convergence rate of the heterogeneous reservoir solution. After that, the point source is used as a building block for obtaining an uniform flux solution of the limited entry vertical well in a heterogeneous reservoir. The solutions developed with the integral transform are compared against classical analytical solutions as well as numerical simulation.